Elucidating the genetic diversity using SSR based markers in Gojri buffalo - SINGH, NARENDRA PRATAP; VOHRA, VIKAS; DAS, RAMENDRA; VERMA, UMAKANT; TANTIA, M S; KATARIA, R S (The Indian Journal of Animal Sciences, 2019)
A population based study was conducted in a large sample of Gojri buffalo, a less known dairy buffalo from Northern India, to assess its genetic variations using 25 heterologous simple sequence repeats (SSR) marker loci. Primers for markers used in the study were labelled either with VIC, NED, PET or FAM dye. Genotyping of each sample was performed by sequencing the PCR amplicons and thereby, estimating diversity indices based on frequency of different allele sizes. Gojri buffalo had an average of 8.2 alleles per locus with 3.65 mean effective number of locus. The polymorphic information content (PIC) values for studied SSR markers ranged from 0.11–0.81, indicating that all the markers, except ILSTS 19, were informative and suitable for the diversity analysis in the buffalo population. The average observed heterozygosity (Ho) and unbiased expected heterozygosity (uHe) estimate were 0.67 and 0.70, respectively in the population with majority of the markers showing Hardy Weinberg equilibrium. A higher expected heterozygosity in Gojri population indicates presence of sufficient genetic diversity, and a higher overall mean of Shannon’s information index (1.5) support these findings. Moreover, both genetic Bottleneck and Mode Shift analysis indicated absence of genetic bottleneck in the recent past among the studied Gojri population. Population inbreeding estimates (FIS=0.029) indicated an average deficiency of 2.9% and suggests no probable inbreeding in the population. It can be concluded that there is presence of sufficient genetic variations in Gojri population and this information can augment in designing its breeding and conservation programme.